Macroscopic and microscopic characterization of the reproductive glands of the male llama (Lama glama) - Mendoza T., Galy (2012)
The macroscopic and microscopic structure of the sexual glands of the reproductive tract of the male llama was characterized using eight adult animals. The macroscopic study was done in situ and using extracted organs and samples collected for histological evaluation. The macroscopic examination revealed the presence of two ampoules originating from the vas deferens, the absence of seminal vesicles, and a prostate gland with lobed body, isthmus and a disseminated portion, and two bulbourethral glands. Dilation of the final portion of the vas deferens suggests the presence of ampoules with glandular characteristics. The prostate body has lobular-like shape but without clear delimitations and shows extensions to the urethra in the form of stalks clearly defined in the disseminated portion. The weight and size of the prostatic lobes indicate that there is more glandular mass in the left lobe. The prostatic acini are surrounded by abundant trabeculae connective tissue infiltrated from the capsule tissue. Prostatic ducts have different presentations at their mouths. The two bulbourethral glands are symmetric in size and weight, and are surrounded by abundant skeletal muscle and little connective infiltration tissue. The ducts of the bulbourethral glands drain into a diverticulum that is directed toward the free portion of the penis. It is concluded that the male lama presents certain macroscopic and microscopic particularities in relation to the distribution and mouths of the sexual glands.